Renato russo : rastros poéticos de um animal sentimental - Alves, Luciano Carneiro (2023)
This thesis proposes a reading of Renato Russo's work as a singular-plural artist within the scope of rock music created in Brazil, arguing about the specificity of the verses composed and sung by him in the search to offer a message of hope and optimism in the face of his social impasses and personal dilemmas. The artist's record production (with the band Legião Urbana and his two solo albums) is approached, understanding that the album "As Quatro Estações" – “The Four Seasons” - (1989) is the first set of songs in which Renato invites his audience to perceive him with more humanity. A stance that he would not abandon in his following works. His human contradictions are amplified when he finds himself HIV-positive in 1990 and chooses not to publicize it. Taking into account the five albums he released until his death in 1996 (in addition to the collection "Música para Acampamento" – “Music for Camp” - in 1992), the main answer that Renato strives to offer with what he composes or interprets is: one should not lose hope as long as there is the primacy of love among human beings. From this perspective, I understand that in the set of 14 songs of "O Descobrimento do Brasil" – “The Discorevy of Brazil” - (1993) there is the materialization of what Renato Russo built as a poetic, aesthetic and political project. A project that, although its non-negotiable issue was the obstinacy of being recognized as a singular artist, was characterized amidst his contradictions and experiences (artistic and personal).